2015
DOI: 10.1371/journal.pntd.0003457
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Routine BCG Vaccination on Buruli Ulcer Disease: A Case-Control Study in the Democratic Republic of Congo, Ghana and Togo

Abstract: BackgroundThe only available vaccine that could be potentially beneficial against mycobacterial diseases contains live attenuated bovine tuberculosis bacillus (Mycobacterium bovis) also called Bacillus Calmette-Guérin (BCG). Even though the BCG vaccine is still widely used, results on its effectiveness in preventing mycobacterial diseases are partially contradictory, especially regarding Buruli Ulcer Disease (BUD). The aim of this case-control study is to evaluate the possible protective effect of BCG vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…The high homology found with other pathogenic mycobacteria, such as M. leprae and M. ulcerans , might further extend their use as vaccine tools7778. Finally, the generic approach we have presented here can be applied for targeted discovery of antigens to be used in control measures for other infectious disease.…”
Section: Discussionmentioning
confidence: 82%
“…The high homology found with other pathogenic mycobacteria, such as M. leprae and M. ulcerans , might further extend their use as vaccine tools7778. Finally, the generic approach we have presented here can be applied for targeted discovery of antigens to be used in control measures for other infectious disease.…”
Section: Discussionmentioning
confidence: 82%
“…A number of case-control studies allowed for the direct identification of potential risk factors for contracting the disease (Table 2). 6,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] A review article evaluating identified risk factors was published in 2010. 88 …”
Section: Risk Factors and Transmissionmentioning
confidence: 99%
“…98,99 However, no evidence of a protective effect on the risk of developing BU was found in a number of case-control studies. 75,77,82,87 BCG vaccination may at least confer some protection against severe forms of BU.…”
Section: Bacillus Calmette-guérin Vaccinationmentioning
confidence: 99%
“…However, there is no consensus on the current distribution of this mycobacterial disease, except for 12 countries which constitute ⁓34,890 reported cases worldwide from 2007 to 2016 (Simpson et al 2019). Buruli ulcer has become the third most common mycobacterial disease after tuberculosis and leprosy (Phillips et al 2015;Huygen et al 2009). Although it may affect everyone irrespective of ages but the risk is the highest in the children (~15 years old) (Huygen et al 2009) and aged people (>50 years old) (N'krumah et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Buruli ulcer has become a major public health concern due to the lack of specific treatment and preventive measures (Simpson et al 2019;Johnson 2019;Singh et al 2019). Despite the effectiveness of antibiotics against Buruli ulcer, failures of treatment are common and the pathogen is prone to develop resistance (Phillips et al 2015). In addition, there is no effective vaccination available for preventing Buruli ulcer (Phillips et al 2015).…”
Section: Introductionmentioning
confidence: 99%